Performance Evaluation of Regional Rural Banks (RRBs) in India - Chinna, Jarupula (Indian Journal of Finance, 2013)
Regional Rural Banks were established in 1976 under the RRB Act, 1975 and the Regional Rural Banks Act, 1976 under the provisions of an ordinance promulgated on September 26, 1975 with an objective to ensure sufficient institutional credit for agriculture and non - agricultural sectors. The RRBs mobilize financial resources from rural and semi-urban areas, and grant loans and advances, mostly to small and marginal farmers, agricultural laborers, and rural artisans. For the purpose of classification of bank branches, the Reserve Bank of India defines a rural area as a place with a population of less than 10,000 people. The RRBs are jointly owned by the Government of India, the concerned State governments, and sponsor banks. The RRBs yielded positive results in respect of key performance indicators such as number of banks and branches, capital composition, deposits, loans, the trend of investments, current deposit ratio, recovery performance, productivity, NPAs, recovery and financial inclusion. The objective of this paper is to study the performance of regional rural banks in India. Several committees have emphasized the need to improve the performance of these banks, which play an important role in the rural credit market in India. The study is diagnostic and exploratory in nature, and makes use of secondary data. The study found that the performance of RRBs in India has significantly improved over time, as steps for their improvement were initiated by the Government of India after the amalgamation process.